Non-interactive Interactivity: building a seemingly interactive installation - João Tiago Maia de Araújo (2017)
This dissertation aims to improve the knowledge on the mechanisms of interactivity, particularly in regards to interactive installations, through a study of the state of the art, and of known mechanisms of interactivity. This informs the building of a technically non-interactive prototype installation that causes, to those who use it, a perception of responsiveness and interactivity where there is none. It is hoped that, with the example of this project, after an analysis both technical and through the eyes of the user, conclusions will be reached that will demonstrate practical applications of certain mechanisms of interactivity so that, in the future, more artists can create more interesting installations and interactive pieces of art.